Front Cover: Stabilization of Pristine Low Resistive State in a Ruthenium(II)‐Polymer of a Hexadentate Schiff Base Ligand: Synthesis, Characterization, and Application as Non‐Volatile Memory Device (Eur. J. Inorg. Chem. 32/2020). Issue 32 (11th August 2020) - Oberoi, Deepa; Dagar, Parveen; Shankar, Uday; Sahu, Satyajit; Bandyopadhyay, Anasuya
Abstract : The Front Cover shows a hand carrying the non‐volatile memory device obtained by the synthesis of a novel cost‐efficient, redox non‐innocent hybrid polymer of a Schiff base ligand with ruthenium(II)‐metal ion. The emergence of its beautiful fluorescence and uncommon I ‐V characteristics, along with unusual low resistive state as pristine state, long charge‐retention, and good repeatability are depicted. More information can be found in the Full Paper by S. Sahu, A. Bandyopadhyay et al.